Pedagang kaki lima di Kotamadya Palangka Raya : studi tentang peranannya dalam usaha menanggulangi pengangguran - Ghany, A. A. (Universitas Palangka Raya, 1985)
On the role of sidewalk peddlers dealing with surmounting unemployment in Palangkaraya City; report of study.